Prediksi Risiko Kesulitan Keuangan melalui Pengungkapan Lingkungan, Sosial, Tata Kelola (Financial Distress Risk Prediction Through Environmental, Social, Governance Disclosures) - Syuliswati, Atika; Nugrahani, Novi; Asdani, Andi; Prasetya, Rizky (Akutansi Bisnis & Manajemen ( ABM ), 2024)
The purpose of this investigation is to predict bankruptcy through the utilization of ESG disclosures. This study examines the influence of disclosure ratings on the financial distress risk of businesses listed in the Sri Kehati index from 2018 to 2022. It concentrates on the impact of disclosure scores on governance performance, social performance, and environmental performance. Panel data regression served as the methodology for the investigation, which included fourteen organizations. The independent variable is the environmental, social, and governance performance disclosure score, while the Altman Z-score proxy measured financial distress risk. The research uncovered a significant negative correlation between the disclosure of environmental performance and the risk of financial hardship. Furthermore, it identified a robust positive correlation between the risk of financial distress and social performance. There is no significant correlation between the disclosure of governance performance and the likelihood of financial hardship.